Knowledge Management System for Zakat - Aulia Rahman Nasution; Irman Hermadi; Wisnu Ananta K.; Irfan Syauqi B. (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Zakat is one of the Islamic pillars that has strategic contribution to the society. Zakat is one of the  Muslim obligation. It is also a form of social solidarity. The collaborative research conducted by Badan Amil Zakat Nasional (BAZNas) and Institut Pertanian Bogor (IPB) estimated the potential of zakat collection in Indonesia could reach about Rp 217 trillion every year that has not been achieved yet. Researchers and practitioners have advised to implement a Knowledge Management System (KMS) to optimize the collection and BAZNas’s objectives. The objective of this research is to develop web-based Zakat Knowledge Management System (ZKMS). The KMS development methodology is done with using Knowledge Management System Life Cycle (KMSLC). Knowledge has been captured from experts consisting of practitioners and scientists from BAZNas of Bogor City, muzakki, documents, books and journals. ZKMS was developed using ASP.NET framework, C# programming language and MySQL database management system. The system has menu that are user, zakat knowledge, questions and answers with experts, interaction between members, about us, profiles and knowledge sources. This system is designed be user friendly to get, know, make, share, store and disseminate actual and contemporary of zakat knowledge. http://dx.doi.org/10.11591/telkomnika.v12i12.6842